Comparing patient satisfaction and intubating conditions using succinylcholine or low-dose rocuronium for rigid bronchoscopy: a randomized study - Ghezel-Ahmadi, Verena; Beck, Grietje (The thoracic and cardiovascular surgeon, 2015)
Introduction: Despite its serious side effects, succinylcholine is commonly used for neuromuscular relaxation in short procedures, such as rigid bronchoscopy and tracheobronchial interventions. The application of low-dose rocuronium reversed by low-dose sugammadex might be a modern alternative. The aim of this study was to compare patient satisfaction, incidence of postoperative myalgia (POM) as well as intubating conditions of these two muscle relaxants for rigid bronchoscopy.